First report of Paraphaeosphaeria angularis as endophyte in sugarcane (Saccharum officinarum) from India - MALARVIZHI, K; MURALI, T S; KUMARESAN, V (The Indian Journal of Agricultural Sciences, 2022)
Sugarcane (Saccharum officinarum L.) is considered to be an important crop that is utilized for production of molasses, sugar and ethanol. Thus, identifying microbes associated with this crop plant will give more insight into plant-microbe interaction. Further, there are limited studies on sugarcane fungal endophytes. Therefore, sugarcane leaves obtained from approximately 3 month old sugarcane plants growing in Puducherry were screened for the presence of fungal endophytes, during March 2022. The study conducted to identify fungal endophytes of sugarcane resulted in isolation of a sterile form which was identified as Paraphaeosphaeria angularis, an ascomycetous fungal species, based on sequencing of the internal transcribed spacer and the 5.8S rDNA region. Maximum Likelihood method was used to infer the evolutionary history. It is the first report of this fungus, as endophyte, from sugarcane host from India. The genus Paraphaeosphaeria is known to include plant pathogens, biocontrol agents and endophytic fungi. This study highlights the importance of studying and assigning taxa to the sterile forms especially from crop plants, since a species belonging to Paraphaeosphaeria, viz. P. michotii is reported as a pathogen from sugarcane from other countries. Further studies will reveal the potential of P. angularis as fungal species known to occur just as an endophyte or a capable pathogen.